2011
DOI: 10.1161/circinterventions.110.960187
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Effects of Different Aspirin Dosing Regimens in Type 2 Diabetes Mellitus Patients With Coronary Artery Disease

Abstract: Background-Patients with type 2 diabetes mellitus (T2DM) have reduced aspirin-induced pharmacodynamic effects. This may be attributed to increased platelet turnover rates resulting in an increased proportion of non-aspirin-inhibited platelets during the daily dosing interval. The hypothesis of this study was that an increase in the frequency of drug administration [twice daily (bid) versus once daily (od)] may provide more effective platelet inhibition in T2DM patients. Methods and Results-T2DM patients with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
2
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(104 citation statements)
references
References 33 publications
4
92
2
6
Order By: Relevance
“…Once-daily administration of low-dose ASA may be associated with incomplete inhibition of platelet COX-1 activity and thromboxane-dependent function in diabetics [3,4,23,26]. In the present study, despite the lack of simple linear relationship between plasma concentrations of SA and the S-TxB 2 , we found lower concentrations of SA in several groups of patients selected based on empirical cut-off points for S-TxB 2 .…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Once-daily administration of low-dose ASA may be associated with incomplete inhibition of platelet COX-1 activity and thromboxane-dependent function in diabetics [3,4,23,26]. In the present study, despite the lack of simple linear relationship between plasma concentrations of SA and the S-TxB 2 , we found lower concentrations of SA in several groups of patients selected based on empirical cut-off points for S-TxB 2 .…”
Section: Discussioncontrasting
confidence: 53%
“…Based on these considerations, we calculated ASA dose in mg/kg of body weight, and we found that lower dose of ASA based on the ASA dose per kg of body weight can predict higher S-TxB 2 concentrations. As it was suggested by others, the higher doses or twice daily dosing of ASA may overcome the reduced platelet response to ASA, thus increased platelet reactivity, observed in diabetic patients [3,26].…”
Section: Discussionmentioning
confidence: 73%
“…34 Based on the above data, it has been proposed that certain high-risk patient populations might benefit from diagnostic screening for tailored antiplatelet therapy. In a small study conducted by Capodanno et al, 75 30 patients with type 2 diabetes mellitus and coronary artery disease underwent a weekly aspirin dose and/or frequency escalation scheme followed by platelet functional testing using the VerifyNow assay. Platelet function was tested in each patient after 1 week of either daily aspirin at a dose of 81 mg, 162 mg, or 325 mg, or twice-daily aspirin at a dose of 81 mg or 162 mg.…”
Section: Post-coronary Artery Bypass Graft Surgerymentioning
confidence: 99%
“…Similar to the findings of Rocca et al, 34 twice-daily aspirin was associated with more platelet inhibition than once-daily aspirin. 75 Neubauer et al 76 recently studied a dose escalation and subsequent therapeutic substitution algorithm in aspirin and clopidogrel nonresponders in patients undergoing PCI for ACS or stable angina. Patients underwent whole-blood aggregometry to both ADP and arachidonic acid.…”
Section: Post-coronary Artery Bypass Graft Surgerymentioning
confidence: 99%
“…75 mg per day). Previous studies demonstrated that T2DM patients treated with 162 mg ASA had lower incidence of HPR than those receiving 81 mg, however increasing the dose to 325 mg had not resulted in further improvement in terms of platelet reactivity [14,15]. Also in the AVOCADO study switching to higher dose of ASA reduced platelet reactivity in T2DM patients with HPR initially treated with 75 mg of ASA per day [16].…”
Section: Introductionmentioning
confidence: 96%